Prophetic Communication: Implementation of Da'i Da'wah Strategies in The Millennial Era - Irawan, Gusli Bambang; Radiamoda, Anwar (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2023)
As technology advances, the da'wah model used by preachers is becoming more dynamic. The increasingly rapid development of the times requires da’i to change their preaching strategies to make them more relevant to the millennial generation who are familiar with advances in information technology. The new media phenomenon can be applied to spread Islam in the millennial era. One of the da'wah strategies that is relevant in this millennial era is the concept of prophetic communication. This research aims to find out how prophetic communication is used as a concept and strategy for da'wah and how prophetic communication is applied to preachers in the millennial era. This research uses bibliographic methods in several journals and books related to this discussion. The conclusion of this research is that prophetic da'wah in the millennial era emphasizes humanization, social justice and dimensions of spirituality. Adapting messages to the social context and use of mass media is important. Information technology is used to reach a wider audience while enriching religious knowledge with other knowledge. Data supports social change, while social media is used as an effective means of preaching. Da'i need to continue learning, following developments with the times, while maintaining Islamic values ​​in prophetic communication. Adapting da'wah to changing times and technology is very important. Seiring kemajuan teknologi, model dakwah yang digunakan para da'i semakin dinamis. Pesatnya perkembangan zaman menuntut para da’i mengubah strategi dakwahnya agar lebih relevan dengan generasi milenial yang akrab dengan kemajuan teknologi informasi. Fenomena media baru dapat diterapkan untuk menyebarkan Islam di era milenial. Salah satu strategi dakwah yang relevan di era milenial ini adalah konsep komunikasi profetik. Penelitian ini bertujuan untuk mengetahui bagaimana pemanfaatan komunikasi profetik sebagai konsep dan strategi dakwah serta bagaimana penerapan komunikasi profetik pada para da’i di era milenial. Penelitian ini menggunakan metode kepustakaan pada beberapa jurnal dan buku yang berkaitan dengan pembahasan ini. Kesimpulan dari penelitian ini adalah Dakwah profetik di era milenial menekankan humanisasi, keadilan sosial, dan dimensi spiritualitas. Adaptasi pesan dengan konteks sosial dan penggunaan media massa menjadi penting. Teknologi informasi digunakan untuk menjangkau khalayak lebih luas sambil memperkaya ilmu agama dengan ilmu lain. Data mendukung perubahan sosial, sementara media sosial dijadikan sarana dakwah yang efektif. Para da'i perlu terus belajar, mengikuti perkembangan zaman, sambil menjaga nilai-nilai Islam dalam komunikasi profetik. Adaptasi dakwah dengan perubahan zaman dan teknologi sangat penting.